2009
DOI: 10.1051/0004-6361/200911915
|View full text |Cite
|
Sign up to set email alerts
|

Low-amplitude variations detected by CoRoT in the B8IIIe star HD 175869

Abstract: Context. The origin of the short-term variability in Be stars remains a matter of controversy. Pulsations and rotational modulation are the components of the favored hypothesis. Aims. We present our analysis of CoRoT data of the B8IIIe star HD 175869 observed during the first short run in the center direction (SRC1). Methods. We review both the instrumental effects visible in the CoRoT light curve and the analysis methods used by the CoRoT Be team. We applied these methods to the CoRoT light curve of the star … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…2 we display the Fourier spectrum, showing the typical aliasing at the orbital frequency (as described in Gutiérrez-Soto et al 2009). From the frequency analysis, we obtain 60 significant frequencies which are listed in Table 2.…”
Section: Frequency Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…2 we display the Fourier spectrum, showing the typical aliasing at the orbital frequency (as described in Gutiérrez-Soto et al 2009). From the frequency analysis, we obtain 60 significant frequencies which are listed in Table 2.…”
Section: Frequency Analysismentioning
confidence: 99%
“…All the techniques used in this paper are described in detail by Gutiérrez-Soto et al (2009). As mentioned in that paper, the orbital characteristics of the CoRoT satellite produces signal in the data at the orbital frequency (13.97 cd −1 , 161.689 μHz) and day/night peaks (2.007 cd −1 , 23.229 μHz) and their harmonics.…”
Section: Frequency Analysismentioning
confidence: 99%
“…Since the noise decreases with frequency, it can thus miss peaks at high frequencies with S /N > 4 but low amplitudes. For a detailed description of these methods, we refer to Gutiérrez-Soto et al (2009). Frequencies found with these 3 methods, their amplitude and phase, as well as the interpretation of each frequency in terms of stellar signal or combinations, but excluding instrumental frequencies such as the orbital frequency of the satellite, are given in Table 5.…”
Section: Corot Photometric Datamentioning
confidence: 99%
“…The amplitudes and phases, and their errors, obtained for each set of frequencies with these three methods were recalculated with Amphi to achieve greater accuracy and homogeneity and are also given in Table 5. For a complete set of fixed frequencies, this program calculates the amplitudes and phases to obtain the best fit to the light curve (see Gutiérrez-Soto et al 2009). …”
Section: Corot Photometric Datamentioning
confidence: 99%
“…A remarkable finding is the outburst signal detected in the B0.5IVe star HD 49330 (Huat et al 2009), a phenomenon that has not been observed to occur in any of the other observed Be stars, which are of later spectral type. Theoretical work is needed to understand and interpret the observed frequency patterns in the Be pulsators (Neiner et al 2009;Diago et al 2009;Gutiérrez-Soto et al 2009). Progress is hampered by the mathematical complexity of describing the oscillations in these flattened stars, induced by their rapid rotation, often close to their critical velocity.…”
Section: Introductionmentioning
confidence: 99%